Situation, trends and prospects of electric power supply in Africa - United Nations (New York: United Nations, 1966)
This study represents a first attempt to evaluate the many-sided problems of electric power development throughout a continent comprising 50 distinct territories.
"United Nations publication sales no.: 65.ll.K.2"
ne 10/05/2018
Loans
Keywords: Electric utilities; Power resources; Electric Power Production; Africa